STUDI HUBUNGAN ANTARA MODAL MANUSIA, MODAL SOSIAL, DAN MODAL KEUANGAN DENGAN STRATEGI INOVASI PERUSAHAAN UKM - Wihalminus Sombolayuk; Ria Mardiana Yusup; Indrianty Sudirman (SIMAK, 2019)
This study draws on the conceptual framework of the relationship between human capital and innovation strategies and the relationship of social capital on innovation strategies and the relationship between financial capital and innovation strategies. This research is a literature study and the development of a conceptual framework on SMEs as an analysis. The results of the study succeeded in formulating three prepositions, namely a) a positive relationship between human capital and the company's innovation strategy; b) positive relationships between social capital and SME company innovation strategies; c) positive relationships between financial capital and the company's innovation strategy. The higher human capital, social capital, and financial capital, the better the formulation and implementation of innovation strategies in SME companies.